Tracking the Historical Track of Java Woe (Java Tribe) in Bei Wali Village, Bajawa District, Nagafa Regency, Flores NNT - Nong Hoban; Agustinus Bhara; Damianus Rikardo Sumbi Wasa (Universitas Muhammadiyah Enrekang, 2022)
The problem raised in this paper is as follows: how is the origin of Woe Jawa (Javanese) in Beiwali Village, Bajawa District, Ngada Regency, NTT. The purpose of writing is to describe the history of Woe Jawa (Javanese) in Beiwali Village, Bajawa District, Ngada Regency, NTT. The research method used is qualitative research. Data collection techniques are interviews, observation, and documentation. Data analysis techniques are as follows: data reduction, data presentation, and drawing conclusions. The results show that the historical traces of Woe Jawa (Javanese) in Beiwali Village, Bajawa District, Ngada Regency, NTT are told on a long journey from their ancestral land, woe Jawa (Javanese) came from the Back Indies (Yunan). At that time it was estimated that the ancestors of Woe Jawa (Javanese) were pressured by other tribes so that they looked for a better life. On the way, they broke through the wilderness and crossed the ocean and stopped at several places before entering the island of Flores, the land of Ngada, among others: Sumatra, Java in the land of Java, the ancestors of the Javanese woe lived a long time and had children and grandchildren and then migrated to Sumbawa. then they go to Wio (Sumba) in Sumba they live sedentary for a while then they go to tiwa lina (calm and shady beach) Aimere beach (wae mokel) Flores Island, when the wae mokel river overflows the ancestors of woe Jawa (Javanese) moved to the east settled in Bo Jawa Meze (location of Aimere) and then they moved to Tana Dua (fertile land). The fertile land in question is the land of Ngada.